Variation of Particle Size with Copper Content in Copper Cobalt Ferrite. Issue 1 (19th August 2020) - Karande, Subash S.; Kavale, Mahendra S.; Pushpanjali, Gurubasappa M.; Karche, Bhanudas R.
Abstract: Nanoparticle size polycrystalline aluminium substituted copper cobalt ferrite samples Cux Co1‐x Fe2‐2y Al2y O4 (where x = 0.0, 0.2, 0.4, 0.6, 0.8, 1.0; y = 0.05, 0.15, and 0.25) have been prepared by standard ceramic technique. The effects of aluminium and copper on structural properties of cobalt ferrite are studied. A universal testing machine as well as Archimedes' method is applied for determining the physical properties of the samples. Phase formation is investigated using x‐ray diffraction, infrared absorption technique, and scanning electron microscope technique. The size of particle raises with the increase in concentration of Al 3+ content. The particle size occurs in the nano range 50–100 nm. The particle size is a very important parameter in terms of ferrite.